Upaya Peningkatan Pemahaman Konsep Relasi dan Fungsi dengan Metode Game Interaktif dalam Pembelajaran Matematika di Kelas 8A SMP Negeri 9 Kota Blitar - Yuliati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
The importance of learning mathematics in everyday life is very interesting and a challenge to learn, because mathematics is a science that is obtained from the thought process, so to build mathematical concepts cannot be instant or fast. There needs to be a process of planting concepts that is carried out gradually in learning mathematics. In learning Relations and Functions in Class 8A of SMP Negeri 9 Kota Blitar, in the 2022/2023 academic year, it can be seen that there are still many students who do not understand Relations and Functions. It can be seen that from 32 students there are 10 students who achieve completeness or 31%, these results indicate that the teacher has not been successful in carrying out learning. To improve learning by conducting a Classroom Action Research using a learning method so that students can understand the concept. The learning method used is the Interactive Game method, which is a game in learning that can foster students' understanding of concepts and make students not bored in learning.